KEPEMIMPINAN NON-MUSLIM DALAM PERSPEKTIF IMAM AL-MAWARDI (KAJIAN LITERATUR KITAB AL-AHKAM AS-SULTHANIYYAH) - Sutisna Sutisna; Evan Edo Prasetya; Yono Yono (DIKTUM: Jurnal Syariah dan Hukum, 2021)
This study aims to see the views of Imam al-Mawardi about the leadership of a non-Muslim as stated in his book entitled Al-Ahkam As-Sulthaniyyah. This research is a theoretical normative legal research and the approach is normative juridical research. Research that uses data by conducting literature studies, book documentation, written archives related to the object of research.